A kind of heat-insulating aerogel material and its preparation method and application

By doping aluminum and yttrium in silica aerogel materials and combining specific oxysilane-modified and modified graphene oxide/titanium dioxide composite materials, the problem of aerogel materials being easily sintered at high temperatures is solved, and the high temperature stability and thermal insulation performance are improved, while improving mechanical properties are improved, which is suitable for building materials.

CN118993691BActive Publication Date: 2025-04-25GUANGDONG XINCHANGSHUN NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411111260.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-13
Publication Date
2025-04-25
Estimated Expiration
2044-08-13

AI Technical Summary

Technical Problem

Existing silica aerogel materials are prone to sintering and collapse in structure at high temperatures, resulting in an increase in thermal conductivity and affecting thermal insulation and mechanical properties.

Method used

By doping aluminum and yttrium, stable compounds are formed, framework structure and microstructure are enhanced, thermal conductivity is reduced, and high temperature stability and thermal insulation properties of aerogels are improved by specific oxysilane modification and modification of graphene oxide/titanium dioxide composites.

Benefits of technology

It significantly improves the high temperature stability and thermal insulation properties of aerogel materials, while enhancing its mechanical properties, and is suitable for building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004992893130000121
    Figure BDA0004992893130000121
  • Figure BDA0004992893130000131
    Figure BDA0004992893130000131
Patent Text Reader

Abstract

The invention provides a heat-insulating aerogel material, and the raw materials for preparing the aerogel material include a silicon source, an aluminum source, a yttrium source, oxysilane, propylene oxide, a titanium source, modified graphene oxide, whiskers, and a dispersant. The wet gel is prepared by a ternary doping method, and then a titanium dioxide sunscreen and a zirconium oxide whisker are compounded. The prepared heat-insulating aerogel material has good heat-insulating effect, high thermal stability, and good mechanical properties, and can be applied to the field of building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to a heat insulating aerogel material and a preparation method and application thereof. Background Art

[0002] Aerogel is a solid material with a nanoporous network structure and a gaseous dispersion medium in the pores. It is one of the lightest solids in the world. Its unique structure gives aerogel excellent performance in many fields such as thermal, acoustic, optical, electrical, and mechanical. In the field of construction, aerogel materials have attracted widespread attention due to their excellent thermal insulation properties. With the global emphasis on energy conservation, emission reduction and sustainable development, aerogel materials, as efficient thermal insulation materials, have broad application prospects in building thermal insulation.

[0003] Although aerogel materials have many advantages, they still have certain defects. Silica aerogel is one of the most studied aerogel materials. Although it is easy to prepare and has a certain thermal insulation effect, its mechanical strength is relatively low, it is easily damaged by external forces, and its thermal stability is poor. Therefore, it is necessary to develop a new type of aerogel material that has excellent thermal insulation effect while having certain thermal stability and mechanical strength to meet the needs of building materials. Summary of the invention

[0004] The purpose of the present invention is to provide a thermal insulating aerogel material and a preparation method and application thereof. The thermal insulating aerogel material has good thermal insulation effect, high thermal stability, and good mechanical properties, and can be applied to the field of building materials.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] A heat-insulating aerogel material, the preparation raw materials of which include silicon source, aluminum source, yttrium source, oxysilane, propylene oxide, titanium source, modified graphene oxide, whiskers and dispersant.

[0007] Preferably, the silicon source is one or both of methyl orthosilicate and ethyl orthosilicate.

[0008] Preferably, the aluminum source is aluminum chloride.

[0009] Preferably, the yttrium source is yttrium chloride.

[0010] Preferably, the molar ratio of the silicon source, the aluminum source, and the yttrium source is 1:(1-3):(4-6); more preferably, it is 1:2:5.

[0011] Ordinary silica aerogels are prone to sintering and structural collapse at high temperatures, resulting in a rapid increase in thermal conductivity, affecting its high-temperature thermal insulation and mechanical properties. The inventors found that by doping with aluminum and yttrium, the thermal insulation effect and high-temperature stability of the prepared aerogel material can be improved. This may be because the addition of aluminum and yttrium can not only form stable compounds with the silicon source, enhance the skeleton structure and skeleton strength, thereby improving the high-temperature stability of the aerogel, but also change the microstructure of the aerogel, thereby reducing its thermal conductivity. In addition, the formed yttrium oxide can increase the crystal transition temperature of aluminum oxide, and form a more solid, stable and uniform structural network with silicon dioxide under the action of propylene oxide, further improving the high-temperature stability and thermal insulation performance of the aerogel material. However, only element doping has limited effect on the improvement of aerogel performance.

[0012] Preferably, the oxysilane is methyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0013] Preferably, the mass ratio of the methyltrimethoxysilane to the γ-aminopropyltriethoxysilane is 1:(0.5-2); more preferably, it is 1:1.

[0014] The inventors found that the use of specific oxysilanes to modify the ternary aerogel precursor solution can improve its adhesion to the graphene oxide / titanium dioxide composite material. This may be because by introducing two silane coupling agents, not only functional groups such as amino groups are grafted on the surface of the gel, which can react with the epoxy groups on the graphene oxide, so that the graphene oxide can adhere to the gel, thereby improving its adsorption effect; at the same time, it can react with the hydroxyl groups on the surface of the wet gel, not only grafting hydrophobic groups, thereby changing its surface properties and improving the waterproof performance of the aerogel, but also modifying the inner surface of the aerogel pores, destroying the hydrogen bonding force, making the internal pore structure more stable, and no obvious shrinkage will occur during the drying process, retaining the porous structure.

[0015] Preferably, the titanium source is titanium tetrachloride.

[0016] Preferably, the whiskers are zirconium oxide whiskers.

[0017] Preferably, the diameter of the zirconium oxide whisker is 2-4 μm, the length is 2-40 μm, and the melting point is 2580-2600°C.

[0018] In some preferred embodiments, the zirconium oxide whiskers are purchased from Shandong Deaipu Energy Saving Materials.

[0019] Preferably, the raw materials for preparing the modified graphene oxide include single-layer graphene oxide and multi-layer graphene oxide.

[0020] Preferably, the mass ratio of the single-layer graphene oxide to the multi-layer graphene oxide is (1-3):1; further preferably, it is 2:1.

[0021] Preferably, the single-layer graphene oxide includes a first single-layer graphene oxide and a second single-layer graphene oxide.

[0022] Preferably, the mass ratio of the first monolayer graphene oxide to the second monolayer graphene oxide is 1:(0.5-2); further preferably, it is 1:1.

[0023] Preferably, the first single-layer graphene oxide has an average thickness of 0.5 to 1.2 nm and a diameter of 4 to 7 μm.

[0024] Preferably, the second single-layer graphene oxide has an average thickness of 0.8 to 1.2 nm and a diameter of 0.5 to 5 μm.

[0025] Preferably, the multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.

[0026] In some preferred schemes, the first monolayer graphene oxide and the multilayer graphene oxide are both purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; the second monolayer graphene oxide is purchased from Jiangsu Xianfeng Nano Materials Technology Co., Ltd.

[0027] In order to further improve the high-temperature stability of aerogel materials, three specific graphene oxides were selected for compounding. This may be because the diameter and thickness of specific graphene oxides are not much different, so there is a certain compatibility between the three. On the one hand, the complementarity in the number of layers is achieved, which not only retains the high activity of single-layer graphene oxide, but also improves the mechanical properties of the product. On the other hand, single-layer and multi-layer graphene oxides of similar sizes are intertwined and stacked to form a stable three-dimensional network structure, which can improve the structural stability of aerogel materials, thereby improving their high-temperature stability. However, the particle size of graphene oxide is too small, and its dispersibility in the system is poor, which affects the uniform distribution of titanium dioxide.

[0028] The preparation method of the modified graphene oxide is as follows: a single-layer graphene oxide and a multi-layer graphene oxide are mixed and evenly dispersed in N,N-dimethylformamide, toluene-2,4-diisocyanate is added, the mixture is stirred at 80-100° C. for 30-40 hours, and the mixture is filtered and dried to obtain the modified graphene oxide.

[0029] Preferably, the solid-liquid ratio of the total mass of the single-layer graphene oxide and the multi-layer graphene oxide to N,N-dimethylformamide is 1 g:15-25 mL; further preferably, it is 1 g:20 mL.

[0030] Preferably, the added amount of the toluene-2,4-diisocyanate is 80 to 100 times the total mass of the single-layer graphene oxide and the multi-layer graphene oxide.

[0031] The inventors found that the use of isocyanate to modify graphene oxide can improve its dispersibility and avoid agglomeration. This is because isocyanate can react with the hydroxyl and carboxyl groups of graphene oxide to form carbamate and amide functional groups. Through the connection of isocyanate, a strong covalent bond can be formed between adjacent graphene oxide nanosheets, thereby improving its dispersibility, so that titanium dioxide can be evenly loaded on its surface. However, considering the agglomeration effect of graphene oxide, its addition amount should not be too much, and excessive agglomerated graphene oxide may block the holes of aerogel materials and affect the thermal insulation effect. Moreover, the adhesion between graphene oxide and ternary aerogel materials is poor.

[0032] Preferably, the dispersant is hydroxyethyl cellulose and chitosan.

[0033] Preferably, the hydroxyethyl cellulose is dissolved in an aqueous solution at 20° C., has a viscosity of 30,000 to 50,000 mP·s when the mass concentration is 2%, and has an ash content of ≤5%.

[0034] In some preferred embodiments, the hydroxyethyl cellulose is purchased from Jinan Kaichuang Chemical Co., Ltd.

[0035] Preferably, the chitosan has a deacetylation degree of 90% to 95%, a viscosity of ≤200 cps, and an ash content of ≤0.5%.

[0036] In some preferred embodiments, the chitosan is purchased from Huantai County Jinhu Crust Products Co., Ltd.

[0037] Preferably, the mass ratio of hydroxyethyl cellulose to chitosan is 1:(3-5); more preferably, it is 1:4.

[0038] The method for preparing the thermal insulating aerogel material comprises the following steps:

[0039] S1, dissolving silicon source, aluminum source and yttrium source in ethanol aqueous solution, stirring at room temperature for 1 to 2 hours, adding propylene oxide, continuing to stir for 5 to 10 minutes, adding oxysilane, continuing to stir for 1 to 2 hours, to obtain solution 1;

[0040] S2. preparing modified graphene oxide / titanium dioxide composite materials;

[0041] S3, adding the modified graphene oxide / titanium dioxide composite material to solution 1 and ultrasonically stirring for 0.5 to 1 hour, adding the dispersant and whiskers, heating to 55 to 65° C. and stirring for 2 to 4 hours, and then standing and aging until the solution gels;

[0042] S4. Soak the gel in anhydrous ethanol for 36 hours, changing the anhydrous ethanol every 12 hours. After soaking, vacuum dry it for 20 to 30 hours to obtain the gel.

[0043] The volume concentration of the ethanol aqueous solution in the present invention is 60% to 70%.

[0044] Preferably, the total molar concentration of the silicon source, aluminum source and yttrium source dissolved in the ethanol aqueous solution is 0.5-1.0 mol / L.

[0045] Preferably, the amount of propylene oxide is 0.8 to 1.2 times the total amount of the silicon source, the aluminum source and the yttrium source.

[0046] Preferably, the amount of the oxysilane is 2 to 4 times the total amount of the silicon source, the aluminum source and the yttrium source.

[0047] The preparation method of step S2 comprises the following steps: dispersing modified graphene oxide in an ethanol aqueous solution, adding a titanium source and ultrasonically dispersing for 2 to 3 hours, adding sodium hydroxide, heat treating at 180 to 200° C. for 20 to 30 hours, centrifuging to obtain a solid, washing the solid with deionized water until it is neutral, and drying it in an oven at 80 to 100° C. for 6 to 10 hours.

[0048] Preferably, the solid-to-liquid ratio of the modified graphene oxide and the ethanol aqueous solution is 1 g: (40-60) mL.

[0049] Preferably, the mass ratio of the modified graphene oxide to the titanium source is 1:(2-4); further preferably, it is 1:3.

[0050] Preferably, the concentration of the sodium hydroxide in the ethanol aqueous solution is 0.003 to 0.005 mol / L.

[0051] The inventors have found that by preparing a modified graphene oxide / titanium dioxide composite material by a specific method, the thermal insulation performance and high temperature resistance of the aerogel material can be improved. The optical properties of titanium dioxide enable it to serve as an effective thermal radiation barrier, which has a thermal insulation effect by reflecting and scattering most of the infrared and other thermal radiation bands, but it is easy to soften and block the aerogel pores at high temperatures. Through a large number of experiments, the inventors have found that by loading titanium dioxide on modified graphene oxide, the thermal insulation performance of the aerogel material can be improved while improving its high temperature resistance. This may be because the modified graphene oxide not only further enhances this reflection and scattering effect and improves the thermal insulation performance of the material, but also the composite of titanium dioxide and modified graphene oxide can further optimize the porous structure of the aerogel material, and reduce the overall thermal conductivity by reducing the thermal bridge effect and enhancing the stability of the pore wall. By loading titanium dioxide on modified graphene oxide, this structure can resist the destructive effect of thermal stress, maintain the integrity and thermal insulation performance of the material, thereby avoiding the situation where titanium dioxide blocks the pores at high temperatures.

[0052] Preferably, the solid-liquid ratio of the modified graphene oxide / titanium dioxide composite material and solution one is 1 g: (80-120) mL.

[0053] Preferably, the added amount of the dispersant is 1% to 3% of the mass of the solution.

[0054] The inventors found that by adding hydroxyethyl cellulose and chitosan as dispersants, it is not only beneficial to the dispersion of zirconia whiskers and synergistically improve the molding uniformity of the aerogel material with the zirconia fibers, but also the hydroxyl and amino groups they carry can form a certain interaction with the wet gel, strengthen the gel skeleton inside the aerogel, and further improve the various properties of the prepared aerogel.

[0055] Preferably, the added amount of the whiskers is 10% to 15% of the mass of the solution.

[0056] Although the aerogel prepared by the above method has excellent thermal insulation performance, it is brittle and easy to break. The inventors found that by adding an appropriate amount of specific zirconium oxide whiskers, the mechanical properties of the aerogel material can be improved while ensuring its thermal insulation performance. This may be because on the one hand, the zirconium oxide whiskers themselves have high mechanical strength and toughness. When they are evenly dispersed and embedded in the matrix of the aerogel, they can form an effective reinforcement network. This network structure can disperse and absorb external stress, thereby preventing the aerogel matrix from breaking and deforming; on the other hand, the high specific surface area and microporous structure of the zirconium oxide whiskers can increase the path length of heat conduction and reduce the efficiency of heat conduction. At the same time, the interfacial thermal resistance between the whiskers and the aerogel matrix will also increase, thereby further hindering the transfer of heat. Moreover, zirconium oxide has a high melting point and can maintain the stability of its structure and performance at high temperatures. In actual experiments, it is necessary to control the size of the zirconium oxide whiskers. If its size is too large and does not match the porous size of the aerogel, it may reduce the porosity of the aerogel to a certain extent, but increase the solid-phase thermal conductivity of the aerogel. In addition, whiskers may be affected by gravity and cause sedimentation. Therefore, on the one hand, the amount of whiskers added needs to be controlled to prevent the increase of thermal conductivity due to excessive addition. On the other hand, the dispersion of the added whiskers in the system needs to be adjusted.

[0057] The thermal insulation aerogel material can be applied to the fields of building materials and the like.

[0058] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0059] 1. The present invention provides a thermal insulating aerogel material. A wet gel is prepared by a ternary doping method, and then a titanium dioxide sunscreen and a zirconium oxide whisker are compounded. The prepared thermal insulating aerogel material has good thermal insulation effect and high thermal stability, and also has good mechanical properties, and can be applied to the field of building materials.

[0060] 2. The present invention prepares modified graphene oxide / titanium dioxide composite materials by a specific method, which can improve the thermal insulation performance and high temperature resistance of aerogel materials.

[0061] 3. The present invention can further improve the high temperature stability of aerogel materials by selecting three specific graphene oxides for compounding.

[0062] 4. The present invention selects a specific oxysilane to modify the ternary aerogel precursor solution, thereby improving the adhesion between the ternary aerogel precursor solution and the modified graphene oxide / titanium dioxide composite material.

[0063] 5. The present invention can improve the mechanical properties of the aerogel material while ensuring its thermal insulation performance by adding an appropriate amount of specific zirconium oxide whiskers.

[0064] 6. The present application further improves the various properties of the prepared aerogel by adding hydroxyethyl cellulose and chitosan as dispersants. DETAILED DESCRIPTION

[0065] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0066] The raw materials used in the present invention are all commercially available, specifically:

[0067] Zirconia whiskers with a diameter of 2-4 μm, a length of 2-40 μm, and a melting point of 2580-2600°C were purchased from Shandong Deaipu Energy Saving Materials.

[0068] The average thickness of the first single-layer graphene oxide is 0.5-1.2 nm, and the diameter is 4-7 μm; the average thickness of the multi-layer graphene oxide is 1-3 nm, the diameter is 4-7 μm, and the number of layers is 2-5; all are purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0069] The second monolayer graphene oxide has an average thickness of 0.8 to 1.2 nm and a diameter of 0.5 to 5 μm, and is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0070] Hydroxyethyl cellulose is dissolved in an aqueous solution at 20° C., and has a viscosity of 30,000 to 50,000 mP·s when the mass concentration is 2%. Its ash content is ≤5%, and it is purchased from Jinan Kaichuang Chemical Co., Ltd.

[0071] The chitosan has a deacetylation degree of 90% to 95%, a viscosity of ≤200 cps, and an ash content of ≤0.5%, and is purchased from Huantai County Jinhu Crust Products Co., Ltd.

[0072] Example 1

[0073] This embodiment provides a method for preparing a thermal insulating aerogel material, comprising the following steps:

[0074] S1. Dissolve tetraethyl orthosilicate, aluminum chloride and yttrium chloride in an ethanol aqueous solution, stir at room temperature for 1.5 hours, add propylene oxide, continue stirring for 8 minutes, add oxysilane, continue stirring for 1.5 hours, and obtain solution 1;

[0075] S2. Preparing a modified graphene oxide / titanium dioxide composite material: mixing the modified graphene oxide and dispersing it in an ethanol aqueous solution, adding titanium tetrachloride and ultrasonically dispersing it for 2.5 hours, adding sodium hydroxide, and heat treating it at 190° C. for 25 hours, centrifuging to obtain a solid, washing the solid with deionized water until it is neutral, and drying it in an oven at 90° C. for 8 hours to obtain a modified graphene oxide / titanium dioxide composite material;

[0076] S3, adding the modified graphene oxide / titanium dioxide composite material to solution 1 and stirring it ultrasonically for 1 hour, then adding the dispersant and zirconium oxide whiskers, heating to 60° C. and stirring for 3 hours, and then standing and aging until the solution gels;

[0077] S4. Soak the gel in anhydrous ethanol for 36 hours, changing the anhydrous ethanol every 12 hours, and vacuum dry it for 25 hours after soaking.

[0078] The molar ratio of tetraethyl orthosilicate, aluminum chloride and yttrium chloride is 1:2:5.

[0079] The oxysilanes are methyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0080] The mass ratio of the methyltrimethoxysilane to the γ-aminopropyltriethoxysilane is 1:1.

[0081] The volume concentration of the ethanol aqueous solution in the present invention is 65%.

[0082] The total molar concentration of the tetraethyl orthosilicate, aluminum chloride and yttrium chloride dissolved in the ethanol aqueous solution is 0.8 mol / L.

[0083] The amount of propylene oxide is 1 times the total amount of tetraethyl orthosilicate, aluminum chloride and yttrium chloride.

[0084] The amount of the oxysilane is 3 times the total amount of tetraethyl orthosilicate, aluminum chloride and yttrium chloride.

[0085] The raw materials for preparing the modified graphene oxide are single-layer graphene oxide, multi-layer graphene oxide, N,N-dimethylformamide and toluene-2,4-diisocyanate.

[0086] The mass ratio of the single-layer graphene oxide to the multi-layer graphene oxide is 2:1.

[0087] The single-layer graphene oxide is a first single-layer graphene oxide and a second single-layer graphene oxide.

[0088] The mass ratio of the first monolayer graphene oxide to the second monolayer graphene oxide is 1:1.

[0089] The preparation method of the modified graphene oxide is as follows: a single-layer graphene oxide and a multi-layer graphene oxide are mixed and evenly dispersed in N,N-dimethylformamide, toluene-2,4-diisocyanate is added, the mixture is stirred at 90° C. for 35 hours, and the mixture is filtered and dried to obtain the modified graphene oxide.

[0090] The solid-liquid ratio of the total mass of the single-layer graphene oxide and the multi-layer graphene oxide to N,N-dimethylformamide is 1 g:20 mL.

[0091] The added amount of the toluene-2,4-diisocyanate is 90 times the total mass of the single-layer graphene oxide and the multi-layer graphene oxide.

[0092] The solid-to-liquid ratio of the modified graphene oxide and the ethanol aqueous solution is 1 g:50 mL.

[0093] The mass ratio of the modified graphene oxide to titanium tetrachloride is 1:3.

[0094] The concentration of the sodium hydroxide in the ethanol aqueous solution is 0.004 mol / L.

[0095] The dispersants are hydroxyethyl cellulose and chitosan.

[0096] The mass ratio of the hydroxyethyl cellulose to chitosan is 1:4.

[0097] The solid-liquid ratio of the modified graphene oxide / titanium dioxide composite material and solution one is 1 g:100 mL.

[0098] The added amount of the dispersant is 2% of the mass of the solution.

[0099] The added amount of the whiskers is 12% of the mass of the solution.

[0100] Example 2

[0101] The difference between this embodiment and embodiment 1 is that the molar ratio of tetraethyl orthosilicate, aluminum chloride and yttrium chloride is 1:1:4.

[0102] Example 3

[0103] The difference between this embodiment and embodiment 1 is that the mass ratio of the modified graphene oxide to titanium tetrachloride is 1:2.

[0104] Comparative Example 1

[0105] The difference between this comparative example and Example 1 is: S1, dissolving tetraethyl orthosilicate and yttrium chloride in an ethanol aqueous solution, stirring at room temperature for 1.5 hours, adding propylene oxide, continuing to stir for 8 minutes, adding oxysilane, and continuing to stir for 1.5 hours to obtain solution 1; the molar ratio of tetraethyl orthosilicate to yttrium chloride is 1:5.

[0106] Comparative Example 2

[0107] The difference between this comparative example and Example 1 is that the molar ratio of tetraethyl orthosilicate, aluminum chloride and yttrium chloride is 1:1:1.

[0108] Comparative Example 3

[0109] The difference between this comparative example and Example 1 is that the oxysilane is methyltrimethoxysilane.

[0110] Comparative Example 4

[0111] The difference between this comparative example and Example 1 is that the amount of the oxysilane is 1 times the total amount of tetraethyl orthosilicate, aluminum chloride and yttrium chloride.

[0112] Comparative Example 5

[0113] The difference between this comparative example and Example 1 is that the modified graphene oxide is a single-layer graphene oxide.

[0114] Comparative Example 6

[0115] The difference between this comparative example and Example 1 is that the mass ratio of the modified graphene oxide to titanium tetrachloride is 1:1.

[0116] Comparative Example 7

[0117] The difference between this comparative example and Example 1 is as follows: S3, adding the modified graphene oxide / titanium dioxide composite material into Solution 1, stirring it ultrasonically for 1 hour, and then standing it to age until the solution gels.

[0118] Comparative Example 8

[0119] The difference between this comparative example and Example 1 is that the dispersant is hydroxyethyl cellulose.

[0120] Comparative Example 9

[0121] The difference between this comparative example and Example 1 is that the graphene oxide is not modified.

[0122] Performance Testing

[0123] The thermal conductivity of the aerogel material at 30°C was tested using a thermal conductivity meter; the thermal stability of the aerogel was tested using a thermogravimetric analyzer, and the mass loss rate of the aerogel material was tested by placing the aerogel material in a nitrogen atmosphere and heating it from 30°C to 1000°C; the compressive stress required for the aerogel material at a strain of 80% was tested using a universal testing machine. The results are shown in Table 1.

[0124] Table 1 Measurement results

[0125]

[0126]

[0127] According to statistics, the thermal insulation aerogel materials prepared by Examples 1 to 3 of the present invention have low thermal conductivity and mass loss rate, and excellent mechanical properties. Comparative Example 1 is not doped with aluminum, Comparative Example 2 has too little yttrium added, Comparative Example 3 does not add γ-aminopropyltriethoxysilane, Comparative Example 4 has too little silane added to the prototype, Comparative Example 5 does not add multilayer graphene oxide, Comparative Example 6 has too much graphene oxide added, Comparative Example 7 does not add zirconium oxide whiskers, Comparative Example 8 does not add chitosan, and Comparative Example 9 does not modify graphene oxide. The thermal insulation aerogel materials prepared have high thermal conductivity and mass loss rate, and low mechanical properties. Therefore, the thermal insulation aerogel materials prepared by the raw materials and methods described in this application have good thermal insulation effect, high thermal stability, and good mechanical properties, and can be applied to the field of building materials.

[0128] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A thermal insulating aerogel material, characterized in that: The preparation raw materials include silicon source, aluminum source, yttrium source, oxysilane, propylene oxide, titanium source, modified graphene oxide, whiskers and dispersant; the molar ratio of silicon source, aluminum source and yttrium source is 1:(1-3):(4-6); the oxysilane is methyltrimethoxysilane and γ-aminopropyltriethoxysilane; the mass ratio of methyltrimethoxysilane and γ-aminopropyltriethoxysilane is 1:(0.5-2); the whiskers are zirconium oxide whiskers; the diameter of the zirconium oxide whiskers is 2-4 μm and the length is 2-40 μm, melting point 2580-2600°C; dispersant is hydroxyethyl cellulose and chitosan; raw materials for preparing modified graphene oxide include single-layer graphene oxide and multi-layer graphene oxide; the preparation method of modified graphene oxide is: taking single-layer graphene oxide and multi-layer graphene oxide and mixing them, and dispersing them evenly in N, N-dimethylformamide, then adding toluene-2,4-diisocyanate, stirring at 80-100°C for 30-40h, filtering and drying to obtain; The modified graphene oxide and the titanium source form a modified graphene oxide / titanium dioxide composite material. The preparation method of the modified graphene oxide / titanium dioxide composite material is as follows: The modified graphene oxide is dispersed in an ethanol aqueous solution, a titanium source is added and ultrasonically dispersed for 2 to 3 hours, sodium hydroxide is added, and a solid is obtained by centrifugation after heat treatment at 180 to 200° C. for 20 to 30 hours. The solid is washed with deionized water until neutral, and then placed in an oven at 80 to 100° C. and dried for 6 to 10 hours to obtain the solid; The mass ratio of the single-layer graphene oxide to the multi-layer graphene oxide is (1-3):1; The mass ratio of modified graphene oxide to titanium source is 1:(2-4).

2. The thermal insulating aerogel material according to claim 1, characterized in that: The silicon source is one or both of methyl orthosilicate and ethyl orthosilicate; the aluminum source is aluminum chloride; and the yttrium source is yttrium chloride.

3. The thermal insulating aerogel material according to claim 2, characterized in that: The multilayer graphene oxide has an average thickness of 1 to 3 nm, a diameter of 4 to 7 μm, and 2 to 5 layers.

4. A method for preparing a thermal insulating aerogel material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, dissolving silicon source, aluminum source and yttrium source in ethanol aqueous solution, stirring at room temperature for 1 to 2 hours, adding propylene oxide, continuing to stir for 5 to 10 minutes, adding oxysilane, continuing to stir for 1 to 2 hours, to obtain solution 1; S2. preparing modified graphene oxide / titanium dioxide composite materials; S3, adding the modified graphene oxide / titanium dioxide composite material to solution 1 and ultrasonically stirring for 0.5 to 1 hour, adding the dispersant and whiskers, heating to 55 to 65° C. and stirring for 2 to 4 hours, and then standing and aging until the solution gels; S4. Soak the gel in anhydrous ethanol for 36 hours, changing the anhydrous ethanol every 12 hours. After soaking, vacuum dry it for 20 to 30 hours to obtain the gel.

5. The method for preparing a thermal insulating aerogel material according to claim 4, characterized in that: The amount of the propylene oxide is 0.8 to 1.2 times the total amount of the silicon source, the aluminum source and the yttrium source; the amount of the oxysilane is 2 to 4 times the total amount of the silicon source, the aluminum source and the yttrium source.

6. Use of the thermal insulating aerogel material according to any one of claims 1 to 3 in building materials.

Citation Information

Patent Citations

  • Preparation method of photocatalytic silicon dioxide aerogel fiber product modified by graphene oxide and with adjustable hydrophilicity and hydrophobicity

    CN108911692A

  • Normal-pressure preparation method of high specific surface area intensive-hydrophobicity graphene oxide / silica composite aerogel

    CN110422850A

  • Ultrathin glass fiber paper-silicon-aluminum-yttrium aerogel composite material and preparation method thereof

    CN116396054A